3D nano-structures for laser nano-manipulation - Seniutinas, Gediminas; Rosa, Lorenzo; Gervinskas, Gediminas; Brasselet, Etienne; Juodkazis, Saulius (Beilstein Journal of Nanotechnology, 2013)
The resputtering of gold films from nano-holes defined in a sacrificial PMMA mask, which was made by electron beam lithography, was carried out with a dry plasma etching tool in order to form well-like structures with a high aspect ratio (height/width ≈ 3–4) at the rims of the nano-holes. The extraordinary transmission through the patterns of such nano-wells was investigated experimentally and numerically. By doing numerical simulations of 50-nm and 100-nm diameter polystyrene beads in water and air, we show the potential of such patterns for self-induced back-action (SIBA) trapping. The best trapping conditions were found to be a trapping force of 2 pN/W/μm2 (numerical result) exerted on a 50-nm diameter bead in water. The simulations were based on the analytical Lorentz force model.
Keywords: extraordinary transmission; near field; optical tweezing; plasmonics; reactive ion etching; self-induced back-action